Structure elucidation, DNA interaction, potential anticancer, molecular docking activities, and γ‐ray irradiation studies on novel mono‐ and binuclear Fe (II), Ni (II), Co (II), and Hg (II) Schiff base complexes. (10th August 2022) - El-Boraey, Hanaa A.; Abdel‐Qader, Aya; Hussien, Mostafa A.
Abstract : Bis Schiff base N, N –((1 E, 2 E )‐ethane 1, 2diylidene)bis(azanylylidene)di(isonicotinohydrazide) ligand L was reacted with Fe (III), Ni (II), Co (II), and Hg (II) chlorides to yield complexes (1–6 ). The structure of the synthesized ligand and metal complexes was well established by various spectroscopic techniques (Fourier‐transform infrared [FT‐IR], UV–Vis., and 1 H NMR), mass spectrometry, elemental analysis (CHN) and physical studies (thermogravimetric analysis [TGA]/first derivative thermogravimetric analysis [DTG], powder X‐ray diffraction, molar conductance, and magnetic moment). Solid powder samples of the binuclear complexes (3 and 6 ) were irradiated at two different irradiation doses (150 and 200 kGy) to yield complexes (3F and 3F* ) and (6F and 6F* ), respectively. For the γ‐irradiated samples, FT‐IR, UV–Vis., and physical studies (TGA/DTG, X‐ray diffraction, molar conductance, and magnetic moment) were performed using the same methods as for the as‐prepared complexes. In addition, calf thymus ct‐DNA binding results monitored by agarose gel electrophoretic method indicated that the as‐prepared binuclear [Hg2 LCl4 (OH)2 ] complex (6 ) and its γ‐irradiated [Hg2 LCl4 (OH)2 ] complex (6F ) have the ability to cleave ct‐DNA at a concentration of 30 and 70 μg/ml, respectively. Inhibitory activity against hepatocellular carcinoma cells (HepG‐2) and breast carcinoma cells (MCF‐7) of ligand and as‐prepared complexes (3, 6, and 6F ) was evaluated. The results revealed that metal complexes exhibited enhanced activity in comparison to the free ligand, and the as‐prepared complex (6 ) shows an IC50 value of 5.7 ± 0.2 and 8.72 ± 0.6 μg/ml for the two cell lines, respectively. Docking process for the ligand and complexes (3 ) and (6 ) with liver cancer protein (ID: 4FM9) and breast cancer protein (ID: 1H7K) has been evaluated. Abstract : A new Schiff base ligand and its complexes (1–6 ) were synthesized and characterized; binuclear complexes Co (II) (3 ) and Hg (II) (6 ) were irradiated by γ‐rays at two different doses. ct‐DNA binding results indicated that the as‐prepared binuclear complex (6 ) and its γ‐irradiated complex at 150 kGy (6F ) have the ability to cleave ct‐DNA, which is consistent with cytotoxicity tests. Docking process showed that Hg (II) complex (6 ) has the best docking score.